Controlled electrochromic effect of liquid crystal cell with j-aggregates - Piryatinskii, Yu.; Nazarenko, V.; Yatsun, O. (Energy and Automation, 2025)
Organic dye molecules dissolved in the liquid crystal (LC) cell were studied by spectroscopic and optical observations. It was shown that the LC cell is a right matrix for organic dye molecules association into submicron size particles (J-aggregates). Nematic liquid crystal matrix arranges J-aggregates in isomorphic way to LC molecules orientation. External electric voltage of higher frequency, applied to LC cell, directs J-aggregate’s chains along applied field and perpendicularly to cell’s surface. External electric voltage of lower frequency destroys J-aggregates to monomers. Key words: nano-size organic dye particles, J-aggregates involved in liquid crystal matrix, association of dye molecules, controlled association and dissociation